Institutional investor cliques and governance - Crane, Alan D.; Koch, Andrew; Michenaud, Sébastien (Journal of Financial Economics, 2019)
We examine the impact of investor coordination on governance. We identify coordinating groups of investors (cliques) as those connected through the network of institutional holdings. Clique members vote together on proxy items: a one standard deviation increase in clique ownership more than doubles votes against low quality management proposals. We use the 2003 mutual fund trading scandal to show that this effect is causal. These findings suggest coordination strengthens governance via voice. Coordination, however, also weakens governance via threat of exit. Clique owners exit positions more slowly, and firm value responds negatively to liquidity shocks when clique ownership is high.